Neural Stem Cells : New Perspectives - Bonfanti, Luca; Bonfanti, Luca (IntechOpen, 2013)
Twenty years after the discovery of neural stem cells, the question whether the central nervous system can be considered among regenerative tissues is still open. On one side, deep characterization of neural stem and progenitor cells, their niches, and their progeny in brain neurogenic sites overtly showed that new neurons can be generated in the brain of adult mammals, including humans. On the other side, many problems arise when stem cells encounter the mature brain parenchyma, still hampering the development of efficacious therapeutic approaches with endogenous or exogenously-delivered neural stem cells. This book tries to make the point on these extremely promising, yet unresolved, issues.
English
Keywords: Proteins; Cellular biology (cytology)